Poly(methyl methacrylate)/Graphene Microparticles Having a Core/Shell Structure Prepared with Carboxylated Graphene as a Pickering Stabilizer. Issue 4 (7th December 2015) - Erdenedelger, Gansukh; Dao, Trung Dung; Jeong, Han Mo
Abstract : Two kinds of carboxylated thermally reduced graphenes (carboxylated TRGs) with different lateral sizes are examined as a Pickering stabilizer in the suspension polymerization of methyl methacrylate. The size and the shape of the prepared composite particles are irregular due to agglomeration, more evidently when the larger carboxylated TRG is used. In addition, carboxylated TRG is distributed not only on the surface but also inside the composite particles. It indicates that the carboxylated TRG alone is not a stable Pickering agent. However, a very small dosage of acrylic acid remedies all these issues because acrylic acid interacts with carboxylated TRG and synergizes the stabilizing effect. The compression molded composite of the core/shell poly(methyl methacrylate)/carboxylated TRG particles exhibits a very low percolation threshold of electrical conductivity of 0.03 vol%. It demonstrates that the carboxylated TRG shells of the composite particles effectively form a segregated conductive network throughout the composite. Abstract : Carboxylated graphenes with different sizes are examined as Pickering stabilizers for the preparation of the core–shell PMMA/graphene composite particles by a Pickering suspension polymerization. It is found that a small dosage of acrylic acid can enhance the stability of the Pickering suspension system. The compression molded composite of the core–shell particles exhibits an ultralow percolation threshold of conductivity.